(untitled) - Fowler, Wallace (Menlo Park, California, 1999)
Contents: Statics: vectors, forces, systems of forces and moments, objects in equilibrium, structures in equilibrium,... Dynamics: motion of a point, force, mass, and acceleration, energy methods, momentum methods,...
Keywords: Dynamics,Statics,Mechanics, applied